Antitumor from Several Plant Compounds Against Hepatocellular Carcinoma Cell Line Hep3B: Mini Systematic Review - Wardatul Aini; Azizah Amatu Zikrah; Sutri Wulansari Safril; Zozy Aneloi Noni; Rita Maliza (Jurnal Biologi Tropis, 2023)
Liver cancer is a global health challenge, with more than one million cases expected by 2025. Hepatocellular carcinoma (HCC) is the most common form of liver cancer and accounts for approximately 90% of cases. Nature provides a large source of natural medicines and compounds, one of which is plants. So, this article is made to contain information on the potential of several plants as antitumor agents. The method of preparing articles through literature review studies that collect articles from various sources such as ScienceDirect, google scholar, PubMed and others in the range of 2013 to 2023. There are ten plant bioactive compounds that have been tested in vitro on Hep3B cell lines to see their toxicity. These plant bioactive compounds play an important role in the proliferation phase, cell cycle, and cell apoptosis in liver cancer and have potential as antitumor.